A conceptual framework and a professional development model for supporting teachers' "triple SRL–SRT processes" and promoting students' academic outcomes. Issue 4 (2nd October 2021) - Kramarski, Bracha; Heaysman, Orna
Abstract: To address teachers' difficulties in implementing effective self-regulated learning (SRL) for their professional knowledge and practice as well as for their students' learning, a conceptual framework and a practical model for professional development is proposed that can help bridge theory, practice, and research on teachers' SRL. Expanding on prior dual frameworks that differentiate teachers' own SRL from their self-regulated teaching (SRT), the "triple SRL–SRT processes" framework also distinguishes teacher-focused from student-focused aspects of SRT. Specifically, three types of self-regulation are proposed: (1) teachers self-regulate their own learning as learners (SRL); (2) teachers self-regulate their practice as self-regulated teachers (teacher-focused SRT); (3) teachers activate students' SRL as teachers of SRL (student-focused SRT). To support teachers' self-regulation using this framework, a spiral model of professional development, supported by preliminary research showing positive effects on teachers' SRL–SRT and students' SRL and achievement, is proposed. Conceptual contributions and practical implications are discussed.